Pemanfaatan Ekstrak Daun Mangga (Mangifera foetida L.) sebagai Penurun Asam Urat dalam Biji Melinjo - Pramudia Bagus Dewangga; Ulys Larasati; Siti Salamah (CHEMICA: Jurnal Teknik Kimia, 2016)
Melinjo plants include the types of old plants. Uric acid is the final metabolism result of purine, purine is one of the components of nucleic acids contained in the body of the cell nucleus. Gout disease to result from consume excessive of purine substances. This research to reduce uric acid levels in seeds melinjo order melinjo seeds can be processed into refined products chips with low uric acid using blanching method from mango leaf extract.This research was making young mango leaf extract using distillate water as a solvent. Melinjo seeds that have been peeled after then process blanching is carried out using preliminary heating at a temperature of less than 80-90 °C for 8 minutes, using young mango leaf extract. Water immersion Melinjo is filtered, then analyzed in the Clinical Pathologyn Laboratory University of Gadjah Mada. This research was conducted with seed weight variables 10, 20, 30, 40, 50, and 60 grams. Other variables such as differences in the length of time 20, 40, 60, 80, 100, and 120 minutes. The preliminary data showed that levels of uric acid in the melinjo seed is 222 mg / 100 g.The result of this research was the highest decrease in uric acid levels using variable melinjo seed weight 10 gr with an immersion time of 30 minutes is 17.86%. Using seed weight 10 gr melinjo carried back to the old variable immersion study obtained results decreased levels of uric acid melinjo seed with most optimal immersion time is 100 minutes with a decrease of 18.43989%.